Imperfect information, macroeconomic dynamics and the yield curve: an encompassing macro-finance model - Hans Dewachter (National Bank of Belgium, 2008)
In this paper we estimate an encompassing Macro-Finance model allowing for time variation in the equilibrium real rate, mispricing and learning dynamics. The encompassing model specification incorporates (i) a small-scale (semi-) structural New-Keynesian model, (ii) flexible price of risk specifications, (iii) liquidity premiums in the form of (constant) deviations from (Gaussian) no-arbitrage and (iv) learning dynamics. This model is estimated on US data using MCMC techniques. We find that the encompassing model outperforms significantly standard Macro-Finance models in terms of marginal likelihood and BIC. Three findings stand out. First, unlike standard Macro-Finance models, a substantial fraction of the variation in long-term yields is attributed to changes in the perceived equilibrium real rate. Second, statistically and economically significant learning effects, especially for inflation expectations, are found. Finally, historical decompositions show that the model can replicate the US yield curve dynamics over the period 1960-2007.
Keywords: E43; E44; E52; 330; Imperfect information; New-Keynesian macroeconomic dynamics; equilibrium real rate; affine yield curve models; Neoklassische Synthese; Dynamische Wirtschaftstheorie; Unvollkommene Information; Rendite; Kapitaleinkommen; Theorie; USA